English textbooks evaluation for the seventh grade - Diba Ratu Vidari Jannah; Rr. Hasti Robiasih (Journal of English Language and Pedagogy, 2019)
The objective of this study are to: (1) find out whether the English textbooks of Mandiri and Solatif for seventh grade have fulfilled the criteria of good textbook, (2) reveal the suitability of the two textbooks with the 2013 Curriculum. This research was conducted using evaluation research. The design was employed to obtain information about the conformity between the basic competences in syllabus of 2013 Curriculum with the materials in the English textbooks and also between the criteria of a good textbook by Cunningsworth with the English textbooks. In this study, two English textbooks; Mandiri and Solatif for seventh grade of junior high school were taken to be analyzed. The results showed that Solatif meets three criteria of a good textbook by Cunningsworth. They are aim and approaches, topics, and methodology. It is partly suitable with four categories: design and organization, language content, skills, and political consideration. However it fails to meet one criterion, which is teacher’s book. Mandiri meets none of the criteria of a good textbook by Cunningsworth. It is partly suitable in seven criteria which are aims and approaches, design and organization, language content, skills, topics, methodology, and political consideration. It fails to meet one criterion; teacher’s book. Based on the data got from the conformity of Solatif with the 2013 Curriculum, it can be summarized that the materials in Solatif covers eight KDs for the seventh grade of junior high school, meaning that it accommodates all what is needed by the students for seventh grade of junior high school. Mandiri. It covers seven KDs for the seventh grade of junior high school. Unfortunately, it does not cover one of the last KD.